Essays on structural breaks and stability of the money demand function - Banafea, Waheed A. (Kansas State University, 2012)
This dissertation consists of three chapters. The first chapter surveys recent studies on the stability of the money demand function in selected developing countries. This chapter presents specific details about modeling and estimating the money demand function. Also, reasons behind the mixed results in the literature on the stability of the money demand function are explored as well as providing a guideline for future research on the stability of the money demand function in developing countries. The second chapter empirically investigates the stability of the money demand function in South Korea and Malaysia. The conventional money demand specification and cointegration framework with a single unknown structural break are conducted. The results of the residual-based tests for cointegration reveal that the M1, M2, and M3 demand are stable in the long run in Malaysia. However, there is no evidence of the stability for all three measures of the money demand in South Korea. The results of the residual-based tests suggest that structural breaks in the cointegration vectors are important and need to be accounted for in the specification of the M1, M2, and LF demand in South Korea, where LF includes M2 in addition to the reserves of nonbanking financial institutions and long-term deposits. The third chapter complements the previous chapter. It aims to evaluate the stability of the money demand function in South Korea and Malaysia using a cash in advance model and cointegration framework with one unknown structural break. This theoretical model adds short-term foreign interest rates and real exchange rates in addition to short-term domestic interest rates and real income. Also, the Granger causality and currency substitution analysis are conducted in this chapter. The results of the residuals-based tests indicate that the M2 and LF demand in South Korea, and M1, M2, and M3 demand in Malaysia are stable in the long run. The structural breaks may not be fairly absorbed when a cash in advance model is used for M1 in South Korea. Thus, the residual-based tests suggest that the structural break is still important and needs to be included in the specification of the M1 demand in South Korea.
Keywords: Money demand function; Economics (0501)